Impact of services on the supply chain configuration of sustainable aviation fuel: The case of CO2e emission reductions in the U.S. (10th June 2023) - Martinez-Valencia, Lina; Peterson, Steven; Brandt, Kristin; King, Allyson Beall; Garcia-Perez, Manuel; Wolcott, Michael
Abstract: Aviation contributes to global warming through CO2, non-CO2 compound emissions, and aviation induced cloudiness. A suite of measures is needed to decarbonize the aviation sector, the most important being developing and deploying sustainable aviation fuel (SAF). Considerable interest exists in the impact of policies that incentivize the environmental services provided by SAF, and their influence on the return on investment to secure capital investment for production facilities. This paper uses financial analysis and a system dynamics approach to analyze the effect of various policies on 1) the time required for a project to reach a positive net present value (NPV), 2) the magnitude of the NPV at the end of plant life, 3) investment risk and 4) potential regional supply development. Production of SAF from municipal solid waste through gasification Fisher-Tröpsch in the U.S. is used as a case study, and the U.S. Northwest for regional development. The results indicate that a successful industry deployment entails strong support during the first three years of production to reach a positive NPV metric, after which it might be competitive with market-based initiatives or by leveraging economies of scale. Initiatives that target CO2 e reductions, through criteria or purpose, generate a major impact. Alignment of strategies to increase fuel yield and emission reduction maximize profits. Stacking policies and programs, when maximizing SAF production, reduces the probability of financial loss under 13% for the three plant sizes assessed. This study demonstrates the importance of the valuation and inclusion of environmental services for project success. Graphical abstract: Image 1 Highlights: SAF development entails strong support during the first years of production. Incentives targeting CO2e reductions strongly impact on decision-making criteria. Strategies to increase fuel yield and emission reduction maximize profits. Incentive stacking reduces the probability of financial loss. Inclusion of environmental services is key for the success of SAF projects.